PARADIGMA BARU WACANA AGAMA - Aksin Wijaya (Millah: Journal of Religious Studies, 2008)
Recently, there are so many violence and harsh actions in the name of ‘holding for religious truth’ against the groups that are perceived as deviant and or astray in Indonesia. Ironically, those violence actions were performed by religious groups and organizations. It became more ironic when Religious Council of Indonesia (MUI) that often acts as the God’s executor, does not proclaimed those visible violence as deviant, even MUI seems tend to hush it. These events apparently influenced by a truth-claimed over the interpretation of religion by particular religious group. Eventually, they who claim the truth, always use religion to justify the violence ways against the other groups that are perceived as deviant. This article strongly aims at releasing religion from that kind of claim. Islamic religion should be claim-free from any particular group or organization, because Islam was born for all human being in the universe.